PENGARUH BEBAN PAJAK, KEPEMILIKAN ASING, DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR MULTINASIONAL - Nataly Angeliena; Theresia Hesti Bwarleling (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the effects of tax expense, foreign ownership, and firm size on transfer pricing practices among multinational manufacturing companies. The study employs a quantitative research approach using secondary data obtained from the annual reports of multinational manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling technique based on predetermined criteria, resulting in 30 companies with a total of 90 firm-year observations over three years with final sample after outlier resulting 33 sample. Data were analyzed using multiple linear regression analysis. The findings indicate that tax expense, foreign ownership, and firm size have influence on transfer pricing practices about 20.1% out of all variables that influencing transfer pricing decisions. Specifically, tax expense does not affect transfer pricing decisions, suggesting that companies may not utilize transfer pricing mechanisms as part of their tax management strategies. Foreign ownership also demonstrates a significant effect, indicating that foreign shareholders may influence corporate policies related to intercompany transactions. In addition, firm size does not affect transfer pricing practices, reflecting the greater complexity and operational scale of larger firms may not increase the likelihood of transfer pricing activities. This study contributes to the existing literature by providing empirical evidence regarding the relationship between tax expense, measured by the effective tax rate (ETR), foreign ownership, measured by the proportion of foreign shareholding, and firm size, measured by the natural logarithm of total assets, with transfer pricing practices. Furthermore, the study offers insights into how these factors shape transfer pricing behavior among multinational manufacturing companies in Indonesia.